Preparação e caracterização de O-carboximetilquitosana (OCMQ) para aplicação como adsorvente de metais pesados - Fernanda Guerra Lima Medeiros Borsagli (2015)
The chitosan (CHI) is one of the most abundant polysaccharides available from natural sources used in various applications, such as pharmaceuticals, biomaterials and many others. It is obtained by means of alkaline deacetylation of chitin natural, being reasonably soluble in acid medium, but with low solubility in aqueous solutions with pH < 6.5. However, improvements can be achieved by the introduction of chemical groups in various reaction conditions. In this sense the carboxymethyl-chitosan (CMC) is a good alternative, because it is soluble in aqueous media acids, alkali and physiological, and may be good candidates for the water treatment. The purpose of this research was to synthesize predominantly the carboxymethyl-chitosan (OCMC) by different chemical routes, changing the concentration of the alkaline medium and the finisher of the reaction, characterize it by different methods and define the most suitable for application on the adsorption of Cd2+ and Chromates. Techniques such as XRD, FTIR, TG, DTG, DSC, UV-visible, NMR, Raman and AAS were used. The results in relation to the synthesis of OCMC indicated that the chemical modification of route in relation to the concentration of the alkali and the finisher of the reaction changed significantly the degree of substitution of OCMC produced and its solubility in aqueous medium. In addition, it was noticed that the replacement occurred preferentially in hydroxyl in both carbons 3 and 6 of CHI. In the adsorption process, the results indicated that for cationics, represented in this study by Cd2+, the OCMC was more efficient than the CHI, in reason of the model multi-dentate acquired in training the predominant form OCMC that allows the presence of more sites of ion uptake. However, for oxyanions of the Cr (VI), the CHI presented greater effectiveness, since the adsorption occurs predominantly in polymer amine groups are groupings in both samples and the range of solubility of OCMC in acid media is lower than that of the CHI, occurring there is agglomeration of polymer affecting the adsorption process. Therefore, it is concluded that the OCMC is a promising solution for the water treatment in relation to heavy metal ions, showing be interesting this chemical modification performed.